Comparison of Ultrasonography and Cone Beam Computed Tomography in the Differential Diagnosis of Periapical Lesions: A Prospective Radiopathological Study - Serindere, Gozde; Aktuna Belgin, Ceren; Bulte, Mert; Gursoy, Didar; Salimov, Fariz (UI Scholars Hub, 2022)
Objective: The aim of this study is to evaluate the correlation between ultrasonography (USG) and cone beam computed tomography (CBCT) and the accuracy between histopathological diagnosis and preliminary diagnosis in the diagnosis of periapical lesion. Methods: 20 patients with periapical lesion in the jaw, were included in the study. The presence of expansion or perforation and dimensions of the lesion were performed with CBCT. In the examination of the lesion with USG, shape, echogenicity, vascularization of the lesion and the presence of buccal expansion and perforation, were determined. Subsequently, a biopsy was taken from the lesion for histopathological examination and the final result was compared with the accuracy of the preliminary diagnoses. Results: Kolmogorov-Smirnov test, Wilcoxon test (w) and Cohen’s kappa coefficient (κ) was used to analyze the data. Three of the 4 lesions diagnosed as periapical granuloma as a preliminary diagnosis were confirmed as periapical granuloma in histopathological examination. Periapical cyst was confirmed in histopathological examination of 14 of 16 lesions diagnosed as periapical cyst as a preliminary diagnosis. Mesiodistal (MD) measurements in CBCT measurements were significantly higher than the USG group (p <0.05). There was 100% agreement (p = 0.000) between the evaluation of buccal expansion, buccal perforation, and palatal-lingual perforation between CBCT and USG. Conclusion: It was concluded that the combined use of USG and CBCT can provide the clinician with important information in the diagnosis of periapical lesion.